2016
DOI: 10.1007/s10957-016-1042-7
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Practical Convergence of a Self-Adaptive Penalty Algorithm for Constrained Global Optimization

Abstract: This paper proposes a self-adaptive penalty function and presents a penalty-based algorithm for solving nonsmooth and nonconvex constrained Communicated by Dario Izzo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…We conclude this subsection by stating the following theorem, whose proof is omitted since it is similar to the one presented in [16].…”
Section: Solution Coding and Hybrid Constraint-handling Proceduresmentioning
confidence: 92%
See 3 more Smart Citations
“…We conclude this subsection by stating the following theorem, whose proof is omitted since it is similar to the one presented in [16].…”
Section: Solution Coding and Hybrid Constraint-handling Proceduresmentioning
confidence: 92%
“…The resulting mutated swarm is denoted by Pg . Successively, we apply the self-adaptive penalty approach by [16] to handle the turnover constraint and to guarantee the global optimality of solutions. More precisely, the objective function value at each projected individual in Pg , namely f (x p ), is normalized according to the formula…”
Section: Solution Coding and Hybrid Constraint-handling Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we found that for the instances we use this is not relevant due to the way the initial population is taken uniformly over the level set with a function value of 1. Actually, the algorithm can easily be extended to deal with constrained problems, [1].…”
Section: Firefly Algorithmmentioning
confidence: 99%